2016
DOI: 10.1186/s40677-016-0047-8
|View full text |Cite
|
Sign up to set email alerts
|

Rural earthen roads impact assessment in Phewa watershed, Western region, Nepal

Abstract: Background: This work describes current research being conducted in the Phewa watershed, near Pokhara in Nepal's Middle hills, a moist sub-tropical zone with the highest amount of annual rainfall in Nepal (4,500-5,000 mm). The main purpose of this study is to focus on the increase and impact of rural earthen road construction in the Phewa watershed as part of land use changes over 30 years in one of Nepal's most touristic regions. Research methods were interdisciplinary and based on a combination of remote sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…The construction of the Pokhara-Baglung Highway in the upper part of the catchment (1988)(1989) preceded this period of lake-area decrease. A rapid and accelerating increase in rural road construction in the high-relief upper catchment is amplifying landslide activity [4], which is projected to increase the rate of sediment delivery into Phewa Lake. Vuillez et al (2018) found that, following extreme rainfall in July 2015, 40% of newly triggered landslides intersected a road and 84% were within 40 m of a road.…”
Section: Post-1982 Lake Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The construction of the Pokhara-Baglung Highway in the upper part of the catchment (1988)(1989) preceded this period of lake-area decrease. A rapid and accelerating increase in rural road construction in the high-relief upper catchment is amplifying landslide activity [4], which is projected to increase the rate of sediment delivery into Phewa Lake. Vuillez et al (2018) found that, following extreme rainfall in July 2015, 40% of newly triggered landslides intersected a road and 84% were within 40 m of a road.…”
Section: Post-1982 Lake Areamentioning
confidence: 99%
“…Landslides triggered by heavy rain or earthquakes often lead to fatalities in the monsoon-dominated high-relief Himalayan landscape [1][2][3], and urban expansion is increasing socio-economic exposure to landslides. Additionally, rural road-building without proper geotechnical considerations is associated with an upward trend in landslide occurrences and sediment mobilisation in Nepal [2,[4][5][6]. The highest rates of sediment transport occur during the monsoon, where pore water pressures are high and landslide activity peaks [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There are four distinct hydrological seasons: pre-monsoon (April and May: AP), monsoon (June to September: JJAS), post-monsoon (October and November: ON) and winter or dry period (December to March: DJFM) in the country [46]. The monsoonal rainfall is highly variable over the country (~1000 mm-~4500 mm) and is intense in nature where more than 80% of the annual rainfall occurs in the 4 months of the monsoon [18,47], resulting in landslides, debris flows, flooding and sedimentation, threatening livelihoods and properties in numerous ways [48].…”
Section: Rationalementioning
confidence: 99%
“…In order to evaluate the rainfall variability and to establish the IDF relationship of the region, the historical rainfall data of 11 weather stations were collected from the DHM (Table 1). The region is one of the most studied areas in the country [48][49][50][51][52][53] due to the importance of Phewa Lake that promotes economic activities and biodiversity. However, the study of rainfall patterns, their intensity and impact have not been properly addressed yet.…”
Section: The Panchase Regionmentioning
confidence: 99%
“…In rural Nepal, there has been a prolific growth of earthen road expansion in recent years. Due to the mountainous topography, steep slopes, and weak soils, these poorly constructed rural roads have increased the probability of landslides especially during the heavy monsoonal rainfall (Leibundgut et al, 2016). Therefore,…”
Section: Drivers Of Tree Cover Change and Policy Responsesmentioning
confidence: 99%